Difficulties in Home-Visit Rehabilitation for Elderly Foreign Residents: Interviews with Physical Therapists - Uesugi, Yuko; Saito, Midori (Kokusai Hoken Iryo (Journal of International Health), 2023)
Introduction  With the increase in the number of foreign residents in Japan and the aging of the population, it is expected that there will be more opportunities to provide home-visit rehabilitation to foreign residents are increasing. The purpose of this study was to clarify the difficulties that physical therapists (PTs) face when providing home-visit rehabilitation to elderly foreign residents.Methods  A qualitative descriptive study using semi-structured interviews was conducted with PTs who have experience in providing home-visit rehabilitation to elderly foreign residents.Results  The subjects were 11 PTs (9 males and 2 females), with an average age of 39.3 years and the average years of PT experience 13.7 years. The analysis revealed that the difficulties faced by PTs included 10 categories; [Differences in rehabilitation concepts with foreign elderly], [Difficulty in goal setting], [Lack of multilingual support and access to information on support], [Burden of dealing with non-rehabilitation work], [Building trust through daily communication], [Detailed communication in different languages], [Dealing with cultural differences], [Differences in religion and sensitivity to this topic], [Dealing with elderly foreign residents who are hesitant to contact with Japanese people] and [Anxiety about conducting home-visit rehabilitation due to PT’s preconceived notions about foreigners].Conclusions  Differences in the rehabilitation concepts between Japan and some foreign countries were found as a difficulty faced by PTs. Difficulties due to language differences were significant, and institutional difficulties also existed, such as lack of multilingual support and access to information on support. In addition, by visiting private homes and providing individualized services, PTs sometimes had to deal with problems faced by elderly foreign people other than rehabilitation work. These were considered to make it difficult to implement goal-oriented rehabilitation.